PENGARUH FAKTOR LINGKUNGAN SOSIAL TERHADAP PERILAKU SEKSUAL BERESIKO PADA ANAK JALANAN DI KABUPATEN BANYUMAS TAHUN 2016 - Rahayu, Lina Dwi Puji (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
The increasing population of street children is followed by an increase in cases of sexually transmitted diseases so that they are also vulnerable to the threat risk of contracting HIV AIDS due to risky sexual practice. This study discusses the risky sexual practice of street children in Banyumas. The study aims to identify sexual practice of street children and the factors that influence it, in order to provide input for the planning and implementation of adolescent reproductive health programs particularly homeless youth. This research is explanatory research with cross sectional study involving 144 samples of street children in the district of Banyumas. Determination of the number of samples using the total sample. Theory of Social cognitive used as a framework for analysis of this quantitative research. Collecting data using a structured interview questionnaire as a guideline. Keywords: street children, risky sexual behavior, social environment